Value chains for nutritious food: Analysis of the egg value chain in the Tigray region of Ethiopia - Hirvonen, Kalle; Baye, Kaleab; Headey, Derek D.; Hoddinott, John F. (International Food Policy Research Institute, 2020)
Eggs have high potential for improving nutrition outcomes in low-income countries, yet very few children in such settings consume eggs on a regular basis despite widespread poultry ownership. To redress this disconnect, a number of interventions have been implemented to improve household production of poultry products, as well as caregiver awareness of the nutritional benefits of eggs and other animal-sourced foods. However, very few of these interventions have tried to leverage food markets to improve nutrition, even though most rural people predominantly rely on markets for the majority of their non-staple food consumption. This study was implemented to better understand the constraints to purchasing eggs for consumption by young children in rural Ethiopia, with a view to informing the design of marketoriented interventions that might cost-effectively increase children’s egg consumption. To do so we analyzed secondary datasets on poultry ownership, household and child egg consumption, and retail egg prices to understand egg markets and the egg value chain in Tigray. Similar to other contexts in sub-Saharan Africa, we find that two-thirds of households own poultry, though only onequarter of young children consumed eggs in the past 24 hours. Although markets in Tigray are well integrated – likely because of the important role of egg aggregators – egg prices remain high. A modest consumption level of 2.5 eggs per person per week would cost around 10 percent of the total budget of households in the poorest quintile of households, even though eggs are more affordable than other animal-sourced foods. We find that egg consumption among young children is not constrained by fasting associated with Orthodox Christianity. High prices are likely the main constraint and are a function of low levels of intensification in egg production, which is dominated by backyard poultry systems characterized by high mortality rates and low productivity. Localized increases in egg production will therefore be needed to lower prices, at least in the short to medium term. We hypothesize that extending the presence of private sector poultry input suppliers in Tigray – who provide chicks through semi-independent agents – offers an entry point for increasing production, lowering prices, and increasing consumption. These input suppliers already have a scalable micro- ranchising model that provides strong economic returns to raising poultry. That model could potentially also be leveraged to raise awareness of the nutritional benefits of eggs.